2019
DOI: 10.3389/fpls.2019.00307
|View full text |Cite
|
Sign up to set email alerts
|

One Century of Forest Monitoring Data in Switzerland Reveals Species- and Site-Specific Trends of Climate-Induced Tree Mortality

Abstract: Climate-induced tree mortality became a global phenomenon during the last century and it is expected to increase in many regions in the future along with a further increase in the frequency of drought and heat events. However, tree mortality at the ecosystem level remains challenging to quantify since long-term, tree-individual, reliable observations are scarce. Here, we present a unique data set of monitoring records from 276 permanent plots located in 95 forest stands across Switzerland, which include five m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 130 publications
8
52
2
1
Order By: Relevance
“…Despite the limitations, which consequently limit the interpretation (discussed below), some clear patterns emerged: Annual mortality rates varied considerably across species ranging between 0.06% for oak and 0.22% for Silver fir. While the annual mortality rates equal those found in Swiss forests (Etzold et al 2019), we could not detect any considerable changes across time in the annual mortality rates as had been found in the Swiss study. This may result from the fact that we have not made any specific distinctions, e.g., by ecoregions or elevation (Etzold et al 2019).…”
Section: Annual Mortality Rates and Disturbance Agentscontrasting
confidence: 64%
“…Despite the limitations, which consequently limit the interpretation (discussed below), some clear patterns emerged: Annual mortality rates varied considerably across species ranging between 0.06% for oak and 0.22% for Silver fir. While the annual mortality rates equal those found in Swiss forests (Etzold et al 2019), we could not detect any considerable changes across time in the annual mortality rates as had been found in the Swiss study. This may result from the fact that we have not made any specific distinctions, e.g., by ecoregions or elevation (Etzold et al 2019).…”
Section: Annual Mortality Rates and Disturbance Agentscontrasting
confidence: 64%
“…For trees that experienced crown damage during the 2014 ice storm, the overall mortality rate was relatively low during the three years following the storm, particularly considering that a large proportion of trees in our sample experienced greater than 75% crown loss. The overall annual mortality rate of 2.2% in our study region is more than double the rates reported for managed forests in central Europe, which are generally less than 1% (Etzold et al 2019;12 Neumann et al 2017), but is consistent with mortality rates of ice-damaged trees reported in the North American literature. Following the ice storm in Canada, (Deschênes et al 2019) report an annual mortality rate of 2.3% in a mixed-species old-growth forest 2-6 years after the storm.…”
Section: Discussionsupporting
confidence: 89%
“…We tried to implement an approach of intermediate complexity between simple bucket models and the Richards equations. From a theoretical point of view, the Richards approach is the most state-of-the-art but requires very long calculation times (Fatichi et al, 2016) and is usually implemented in models specifically dedicated to water flow simulations (in Table 5, only one of the models, MAESPA, uses them). Forest ecosystem models generally use simpler approaches such as the bucket model declined in a large variety of forms (Table 5).…”
Section: Rainfallmentioning
confidence: 99%
“…Since climate change affects some tree growth processes positively and others negatively and given the interactions among factors as well as the feedback and acclimation mechanisms, it is not easy to predict the resulting effect on tree growth at a given site (Lindner et al, 2014;Herr et al, 2016). Knowledge about climate change has been acquired based on long-term monitoring studies that are limited to the observed changes (Bussotti and Pollastrini, 2017;Etzold et al, 2019) and on experiments of environment manipulation generally analysing one or two factors at a time for a limited period (Ainsworth and Long, 2005;Norby et al, 2010;Wolkovich et al, 2012;Meir et al, 2015). In order to apprehend the complex functioning of forest ecosystems, the use of processbased modelling is a complementary approach that allows the integration and structuring of the existing knowledge and extrapolations to be made for unprecedented conditions like those projected for the coming decades.…”
Section: Introductionmentioning
confidence: 99%